1987
DOI: 10.1111/j.1471-4159.1987.tb05636.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Phospholipid Synthesis to Schwann Cells and Axons

Abstract: Quantitative electron microscopic autoradiography was used to detect and characterize endoneurial sites of lipid synthesis in mouse sciatic nerve. Six tritiated phospholipid precursors (choline, serine, methionine, inositol, glycerol, and ethanolamine) and a protein precursor (proline) were individually injected into exposed nerves and after 2 h the mice were perfused with buffered aldehyde. The labeled segments of nerve were prepared for autoradiography with procedures that selectively remove nonincorporated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…Axonal Elongation-In previous studies using the compartment model for culture of neurons (25), we detected no cholesterol biosynthesis, as measured by incorporation of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]acetic acid into cholesterol, in axons of rat sympathetic neurons. We have now shown that under normal culture conditions cholesterol is synthesized in the cell body-containing compartment and efficiently transported into the distal axons.…”
Section: Inhibition Of Cholesterol Synthesis In Cell Bodies Impairsmentioning
confidence: 89%
See 3 more Smart Citations
“…Axonal Elongation-In previous studies using the compartment model for culture of neurons (25), we detected no cholesterol biosynthesis, as measured by incorporation of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]acetic acid into cholesterol, in axons of rat sympathetic neurons. We have now shown that under normal culture conditions cholesterol is synthesized in the cell body-containing compartment and efficiently transported into the distal axons.…”
Section: Inhibition Of Cholesterol Synthesis In Cell Bodies Impairsmentioning
confidence: 89%
“…Incorporation of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]Acetate into Cholesterol-Neurons were plated in the center compartment of compartmented dishes and cultured for 14 days. The radioactive cholesterol precursor [1-14 C]acetic acid (10 Ci/ml) was added to the cell body-containing compartment.…”
Section: Materials-[1-mentioning
confidence: 99%
See 2 more Smart Citations
“…A 5 mm segment of the injected left sciatic nerve was excised from the region of the injection and immersion fixed for 24 hr in 4% glutaraldehyde containing 0.2% digitonin (to prevent the extraction of cholesterol in subsequent steps) (Napolitano and Scallen, 1969;Scallen and Dietert, 1969). Nerve segments were then postfixed in Dalton's chrome osmium for 1 hr, dehydrated rapidly in a series of ice-cold graded acetone solutions to maximize retention of lipids (Gould et al, 1987), and embedded in Spurr's resin. Liquid scintillation spectroscopy of acetone solutions revealed that less than 10% of the incorporated label was extracted by these procedures.…”
Section: Morphological Methodsmentioning
confidence: 99%